(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Secondary traumatic stress (STS) among nurses can negatively affect mental health and the quality of patient care, yet studies on this issue in Vietnam remain limited. Objective: To determine the prevalence of STS and its associated factors among nurses in several hospitals in Can Tho City. Methods: A cross-sectional study was conducted among 267 nurses. Data were collected using the 10-item STS scale (ProQOL R-V) via an electronic questionnaire from July to August 2025. Demographic, occupational, and work environment factors were surveyed. Multivariate logistic regression was applied to identify associated factors. Results: The prevalence of high, moderate, and low STS was 6.4%, 46.8%, and 46.8%, respectively. The mean STS score was 24.36 ± 11.6 (SE = 0.71). Significant associated factors included caring for young children, working department (nurses in Pediatrics were at higher risk than those in other departments), years of experience, and occupational stress level (p < 0.05). Conclusion: STS among hospital nurses is a considerable concern with a notable prevalence. Identifying associated risk factors provides a foundation for developing appropriate interventions.